Diagnostic values of 2 different techniques for controversial lumbar disc herniation by conventional imaging examination: 3D-DESS vs. CT plain scan - Liu, Wei; Chen, Jinhua; Zhang, Yanan; Wang, Xu; Zheng, Junwen; Huang, Aibing; Chen, Chunmao; Bian, Jian; Yang, Lei; Li, Haijun (Frontiers in Physiology, 2022)
Background: The aim of this study was to explore the significance of three-dimensional double-echo steady-state (3D-DESS) sequence and multidetector computed tomography (CT) plain scan in the diagnosis of lumbar disc herniation (LDH) remaining controversial in conventional magnetic resonance imaging (MRI), and to compare the efficiency between 3D-DESS and CT in diagnosing controversial patients by conventional MRI. Methods: A total of 61 patients with controversial LDH diagnosed by conventional MRI were collected. Before operation, the disease of these patients was further confirmed by 3D-DESS sequences and continuous CT plain scan from L3 to S1. Finally, for patients whose postoperative curative effect was marked and symptoms were obviously alleviated, the sensitivity, specificity and accuracy. Results: Among, 59 patients with remarkably relieved symptoms after operation were included, and 2 patients with varying degrees of non-remission of pain and partial dysfunction after operation were excluded. The sensitivity, specificity and accuracy of 3D-DESS were 94.6, 100 and 94.9%, respectively, and those of CT were 75.0, 33.3 and 72.9%, respectively. Conclusion: 3D-DESS is a very useful diagnostic method for patients with some special types of LDH that remain controversial in conventional imaging diagnostic methods. Through 3D-DESS, the morphology of lumbosacral nerve roots can be directly observed, which is conducive to the improvement of the sensitivity, specificity and accuracy, thus further reducing the misdiagnosis rate. Moreover, 3D-DESS plays a guiding role in the formulation of operative methods.